Bird communities in agricultural landscapes: What are the current drivers of temporal trends?. (June 2016) - Frenzel, Mark; Everaars, Jeroen; Schweiger, Oliver
Abstract: Bird populations are declining in agricultural landscapes, which is ongoing for decades now. With standardized breeding bird observation data of five years within 2001–2014 from six sites in Central Germany we investigated whether trends in bird abundance are reflected by trends in species richness and whether these trends depend on the landscape context. We further analyzed whether trends and their dependencies on the landscape context differ among species groups according to their particular traits. For most of the groups (farmland birds, large birds, resident birds, short distance migrators, insectivores, granivores and birds of prey) we found declining trends in abundance. However, these trends were not reflected by species richness. In contrast to our expectations, high amounts of semi-natural habitats in the landscape did not buffer the overall negative trends. Surprisingly, bird abundance declined most in landscapes characterized by larger ranges in altitude and initially highest bird abundance in 2001. We conclude that flat landscapes in Central Germany have been utilized with high intensity already for a long time and they simply maintained their already low bird abundance. On the other hand, a recent increase in agricultural intensity in landscapes with marked altitudinal reliefs, and presumably less usability and productivity, causes the drastic declines in bird abundances. Since these strong declines are not related to habitat loss, we assume that changes in the management of agricultural fields are responsible.